New finds of the Carboniferous cephalopods on the territory of Ukraine - Dernov, Vitaly (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2021)
Formulation of the problem. Carboniferous sediments are widespread in Ukraine. Cephalopods remains are not rare in these deposits. However, they are poorly studied. Cephalopods have great importance for the dismemberment and correlation of Carboniferous sediments, as well as for paleogeographic reconstructions. For this reason, their study is very relevant.The history of the study. Mississippian cephalopods of the Donets Basin and Don-Dnipro Downwarp are poorly studied. At the moment, few ammonoids and one nautilid have been determined from the Mississippian of the Don-Dnipro Downwarp. Numerous Mississippian ammonoids are known from the Donets Basin. Nautilids are known only from the Samara Formation (Lower Serpukhovian).Material and research methods. This article is based on the results of a study of Mississippian cephalopods collection from the Donets Basin (Ukraine: Grabove Village and Dokuchayivs’k in the south of the Donetsk Region) and the Don-Dnipro Downwarp (Ukraine: Sumy and Poltava Regions, Bugrovate and Gubs’ke Villages). In addition, allochthonous remains of cephalopods from the moraine of the Dnipro glacial maximum were studied (Ukraine: Poltava Region, Pyvykha Hill nearby Hradyzk Town).Statement of the main material. Orthocerids, oncocerid Culullus sp., actinocerid Antonoceras balaschovi Shimansky, nautilids Pseudostenopoceras sp. and Liroceras sp. have identified from the limestone boulders in the moraine of the Dnipro glacial maximum (Hradyzk). The age of these limestones from the Late Viséan to Serpukhovian.The geographical origin of the limestone debris can be determined by studying the fossils in these rocks. The results of the study of chaetetids and corals (Victor Ohar), brachiopods (Vladystav Poletaev) and cephalopods (author) show that the source of the limestone boulders with Carboniferous fossils situated in the southern part of the Moscow Syneclise.Fragments of conchs of the orthocerids Brachycycloceras scalare (Archiac et Verneuil) are occurred in the black mudstones of the Upper Viséan opened by the boreholes Bugrovativs’ka-160 (depth is 3650.0-3654.0 metres; Bugrovate Village, Okhtyrka District, Sumy Region) and Gubs’ka-2 (depth is 4740.0-4745.0 metres; Gubs’ke Village, Lubny District, Poltava Region). This species is known from the Namurian of Belgium, Viséan of the Czech Republic and Poland and Mississippian of Germany. The collection also contains a fragment of a large conch of actinocerid Rayonnoceras sp. This specimen comes from the limestone B81 of the Mezha Formation (Upper Viséan) exposed in the vicinity of the Grabove Village on the Kalmius River (Donetsk Region). This genus is very widespread in the Mississippian sediments of North America, Western Europe, European part of Russia and China. Previously actinocerids in the Carboniferous of the Donets Basin were not known.Fragments of conchs of indeterminate orthocerids find in the dark gray fine-crystalline Viséan limestones (Dokuchayivs’k, borehole no. 51, depth is 88.0 metres).Conclusions. The study of new finds of Carboniferous cephalopod remains in Ukraine allowed us to confirm the approximate location of the source of the clastic material of the Dnipro glacial maximum moraine. In addition, expand the systematic diversity of the Mississippian cephalopods of the Donets Basin and Don-Dnipro Downwarp.